2022
DOI: 10.1108/agjsr-03-2022-0007
|View full text |Cite
|
Sign up to set email alerts
|

The lived experience of medical students during COVID-19 pandemic: the impact on lifestyle and mental wellbeing

Abstract: PurposeThe paper intends to explore the lived experiences of medical students during the COVID-19 pandemic and its impact on their lifestyles and mental wellbeing.Design/methodology/approachFourteen medical students from the College of Medicine and Medical Sciences, Arabian Gulf University, Bahrain, were enrolled, and their narratives were obtained. Data were analyzed and conducted using Colaizzi’s phenomenological descriptive method of enquiry.FindingsThe analysis identified two themes, along with nine subthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
1
0
2
Order By: Relevance
“…Tıp öğrencilerinin pandemi öncesinde ve pandemi sırasında haftada 3 kezden fazla bazı besinleri tüketme sıklığı (%). (12). Çalışmamızda, sosyoekonomik durumunu kötü olarak bildiren öğrencilerin VKİ artışının daha fazla olduğu anlaşılmıştır.…”
Section: Pandemi öNcesiunclassified
“…Tıp öğrencilerinin pandemi öncesinde ve pandemi sırasında haftada 3 kezden fazla bazı besinleri tüketme sıklığı (%). (12). Çalışmamızda, sosyoekonomik durumunu kötü olarak bildiren öğrencilerin VKİ artışının daha fazla olduğu anlaşılmıştır.…”
Section: Pandemi öNcesiunclassified
“…Qualitative studies have shown that several groups of individuals who experienced distress during the pandemic emerged from this experience feeling more liberated [47,[58][59][60][61][62][63][64][65][66][67][68]. These participant groups varied greatly in terms of demographics and contexts.…”
Section: Ivd Scientific Implicationsmentioning
confidence: 99%
“…Kemampuan seseorang dalam mengelola rasa juga menjadi sinyal kesehatan mental yang baik. Kesehatan mental dimaknai sebagai kemampuan mereka menghadapi berbagai tekanan yang muncul, menciptakan produktivitas serta berkontribusi bagi orang lain (Alzayani et al, 2022). Literatur lain menjelaskan jika kesehatan mental dimaknai sebagai keberhasilan seseorang dalam mengembangkan berbagai aspek (psikis, kecerdasan dan emosional) (Gao et al, 2023).…”
Section: Sumber Diolahunclassified